The Conflict in the Union of Evangelical Christians-Baptists: 1959 - 1963 - Mikhail NEVOLIN (Богословські роздуми: Східноєвропейський журнал богословʼя)
The division that occurred among Evangelical Christians-Baptists in the 1960s is one of the most dramatic pages in the history of evangelicalism in Russia and the USSR. At present, when the historical facts and chronological sequence of those events have been well studied, more attention should be paid to the analysis of the actions of the All-Union Council of Evangelical Christians-Baptists (AUCECB) and the Council of Churches of Evangelical Christians-Baptists (CCECB) during those years. Unfortunately, what we find now is quite one-sided analysis, where the actions of one of the parties in the conflict (depending on the author’s stand) are presented as correct, while the actions of the other side are portrayed as incorrect and destructive. Now that several decades have passed since those events, there is an opportunity to assess more objectively what happed. This article is an attempt at such an objective analysis.